Characterization of Streptomyces sp from oil palm rhizosphere for biological control of Ganoderma boninense - Syed Aripin @ Isa, Shariffah Muzaimah (2013)
The objective of this study was to isolate, screen and identify actinomycetes from the rhizosphere of oil palm for biological control of Basal Stem Rot (Ganoderma boninense), a very destructive disease of oil palm in Malaysia. Rhizosphere samples from top soils of healthy palms amongst the infected palm on laterite, coastal, inland and peat were used in this study. A total of 1050 of actinomycetes was isolated with 355 isolates (33.8 %) from laterite, 235 (23.38%) isolates from peat, 206 (19.62 %) isolates from coastal and 254 isolates (24.19 %) isolated from inland soil with the highest occurrence of actinomycetes was observed in peat area. About 600 isolates of actinomycetes with different morphological appearance and matched the spore-producing and fast growing criteria were tested for their inhibitory effects on G. boninense mycelia growth on dual culture plates. From 600 isolates screened, 13.5% of the isolates showed potential antagonistic activity with more than 80% of Percent Inhibition of Radial Growth (PIRG). Out of this number, 21 isolates showed highest PIRG with observable abnormal growth of G. boninense. The isolates were further tested for their culture filtrates in the form of liquid and powder (freeze-dried) for effect towards G. boninense growth. Culture filtrate from six isolates, in both forms showed inhibition towards G. boninense with intermediate PIRG value (50% to 80%) with similar inhibition rate observed for the standard antifungal agent (Nystatin) at 0.1 mg/ml and 1 mg/ml. Screening of the culture filtrate on Ganoderma plate showed halo zone with diameter 12.5 – 23.5 mm compared to nystatin at 30 mg/ml and 50 mg/ml from four isolates. Lower inhibition activity obtained might be affected by the concentration of bioactive compound available in the supernatant. Four isolates; AGA 043, AGA048, AGA347 and AGA 506 were highlighted for their ability to inhibit and exhibit potential metabolites against G. boninense. Based on their morphological and cultural characteristic, the potential actinomycetes were identified as a member of Streptomyces genus. Analysis of a partial 16S rRNA gene sequence (512 bp) of AGA043, AGA048, AGA347 and AGA506 exhibited a very high level of 16S rDNA sequence similarity (>98%) with sequence related to different Streptomyces species deposited to the database. However the 16S ribosomal DNA amplification of AGA 043 and AGA048 were only able to be identified up to genus level. The 16S ribosomal DNA amplification of AGA347 and AGA506 revealed that the isolates are closely related to Streptomyces hygroscopicus subsp. hygroscopicus and Streptomyces ahygroscopicus with 99% of similarity percentage All of the Streptomyces isolates were formulated in vermiculite to evaluate their ability to reduce disease incidence in oil palm seedlings. Pre-inoculating the seedlings with AGA347 (T3) showed the most effective in suppressing BSR based on 73.11 % of disease reduction compared to standard antifungal producer, Streptomyces nourseii (T5), AGA043 (T1), AGA048 (T2) and AGA506 (T4) with 47.41 %, 30.11 %, 54.83 % and 44.08 % respectively.